The Call for Economic Students to be Introduced with Mediation Course as to Encourage the Usage of Mediation as the Alternative Dispute Resolution in Resolving Issue Relating to Halal Industries in Future - Hanna Ambaras Khan (International Journal of Halal System and Sustainability, 2022)
Halal industry incorporates almost everything like medicines cosmetics, tourism, banking and finance, and etc. The industry is growing fast globally. This paper will look at a different angle of halal industry i.e., dispute resolution with the aim of educating students about mediation through a course at university level. Mediation is one of the ADR process. It involves an impartial third party who uses his skills and knowledge in assisting disputants to communicate and negotiate, so they would come with solutions for their problems. The increment of the usage of mediation in various field including banking and finance calls for this subject to be introduced to students at university levels. In Malaysia, ADR is a compulsory subject for law students. However, the non-law students have no opportunity to learn and acquire knowledge about this process. This paper discusses about alternative dispute resolution in general and in Islam. It also discusses about mediation and Islamic banking and finance in Malaysia. The current litigation system might not able to understand some Islamic elements in certain Islamic products such as in Islamic banking and finance. This paper proposed to introduce mediation as one of the course offered to the students at School of Business and Economics, Universiti Putra Malaysia (UPM). It is important to equip them with the knowledge before they embark on the working environment in economics fields. The objective of this paper is to examine the understanding of students about mediation and their opinion in proposing mediation as a subject. This paper adopts qualitative research method alone. The findings show that the majority of the students support the idea. This paper also suggests a simple module for the course to be offered to the students.